PENGEMBANGAN MODEL EXPERIENCE BERBASIS BUDAYA ANGKOLA UNTUK MENINGKATKAN KETERAMPILAN MAHASISWA DI ABAD 21 - Nashran Azizan; Edy Surya; Johannes Johannes; Maulana Arafat Lubis (IAIN Padangsidimpuan, 2022)
Education in Indonesia must be transformed based on the 21st century era, which resulted in religious, character, intelligent students, and based on the Law on the National Education System in 2003, and Government Regulation of the Republic of Indonesia Number 57 of 2021 concerning National Education Standards. This study aimed to develop a learning model of Angkola Batak culture-based Experience, South Tapanuli, North Sumatra, through teaching practices in micro-teaching courses. This research used the Research and Development research method by applying the Plomp development model. Random sampling used as a sampling technique consisted of 90 students from the Teacher Education of Islamic Elementary School, Institut Agama Islam Negeri Padangsidimpuan in the sixth semester. Data collected used observation and questionnaires assisted by google form. Data analysis used STATCAL software. The results showed discrepancies were found between the program and expectations as well as reality, while students had not fully understood designing lesson plans based on the applicable curriculum, synchronized the design of lesson plans and the practice, and students were not allowed to teach in schools in order to be able to practice theory and practical teaching applications. At the same time, the program study vision is to prepare Islamic Elementary School teachers with Islamic, innovative, competitive, and professional personalities associated with South Tapanuli culture, like the Angkola Batak. So, it is necessary to develop programs to improve students' skills in applying the learning in the 21st century.